Tatalaksana Aritmia: Fibrilasi Atrial - Gede Agus Andika; Asep Sukohar; Ade Yonata (CV. Jasa Sukses Abadi, 2021)
Abstract Arrhythmias are a problem with the rate or rhythm of the heartbeat. The four main types of arrhythmias are premature or premature beats, ventricular arrhythmias, bradiarimia, and supraventricular arrhythmias. Supraventricular arrhythmias are tachycardia (rapid heartbeat) starting at the atrial or atrioventricular (AV). Types of supraventricular outbreaks include atrial fibrillation (AF), atrial flutter, paroxysmal supraventricular tachycardia (PSVT), and Wolff-Parkinson-White syndrome (WPW). Atrial fibrillation is the most common type of arrhythmia. In general, the management of AF patients has 5 objectives: thromboembolic events, coping with AF related symptoms, optimal management of accompanying cardiovascular disease, controlling heart rate, and improving rhythm disturbance. Antithrombotic therapy used for stroke prevention in FA patients includes anticoagulants (vitamin K or AVK antagonists and new anticoagulants or IMR), and antiplatelets. AKB which is not AVK in Indonesia market, that is dabigatran, rivaroxaban, and apixaban. Dabigatran works by dealing directly with trombinlah rivaroxaban and apixabanacas works by presenting the Xa factor.